2009
DOI: 10.1038/mt.2008.264
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Expression of a Mini-dystrophin That Normalizes Skeletal Muscle Force Only Partially Restores Heart Function in Aged Mdx Mice

Abstract: Duchenne muscular dystrophy (DMD) affects both skeletal and cardiac muscle. It is currently unclear whether the strategies developed for skeletal muscle can ameliorate cardiomyopathy. Synthetic mini-/micro-dystrophin genes have yielded impressive skeletal muscle protection in animal models. The 6-kb ΔH2-R19 minigene is particularly promising because it completely restores skeletal muscle force to wild-type levels. Here, we examined whether expressing this minigene in the heart, but not skeletal muscle, could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 46 publications
(64 reference statements)
7
98
0
Order By: Relevance
“…[7][8][9] We found picrosirius red staining of left ventricular tissue to be significantly elevated at all ages beyond 6 months, and it correlated with dystrophin deficiency rather than age. The link between fibrosis and cardiac dysfunction is not a clear one.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[7][8][9] We found picrosirius red staining of left ventricular tissue to be significantly elevated at all ages beyond 6 months, and it correlated with dystrophin deficiency rather than age. The link between fibrosis and cardiac dysfunction is not a clear one.…”
Section: Discussionmentioning
confidence: 66%
“…4 The mdx mouse, with its genetic parallel to DMD, has been widely used as a research model for this disease and has more recently provided insights into the legacy of cardiac dystrophin deficiency. This includes calcium channel dysfunction, 5 adrenoreceptor abnormalities, 6 fibrosis, [7][8][9] ECG alterations, 7,10 and the development of dilated cardiomyopathy in older animals. 8,9,11 The majority of these findings have been drawn from experiments performed at specific ages of mdx mice, compared only to their age-matched controls.…”
mentioning
confidence: 99%
“…Systemic gene transfer using recombinant adeno-associated virus (rAAV) has been shown to be an excellent method of transducing the whole mouse heart in vivo [27]. Bostick et al [35] reported, using intravenous injection of AAV serotype-9 micro-dystrophin vector, an efficient way to transduce the heart of neonatal mdx mice. Their results showed cardiac histopathology improvement without cardiac function normalization.…”
Section: Gene Therapymentioning
confidence: 99%
“…In addition to skeletal muscle, it is also necessary to treat cardiac muscle, as correction of skeletal muscle function in the absence of cardiac expression is likely to exacerbate cardiac dysfunction (Townsend et al, 2008). Studies using both AAV6 and AAV9 to transduce the myocardium of mdx mice with micro-dystrophin have demonstrated high levels of gene transfer associated with improvements in fibrosis, echocardiography, and protection from dobutamine stressinduced acute heart failure (Townsend et al, 2007;Bostick et al, 2008Bostick et al, , 2009Bostick et al, , 2011Shin et al, 2011;Lai and Duan, 2012;Schinkel et al, 2012). As loss of dystrophin expression from smooth muscle results in changes to the vasculature (Loufrani et al, 2001(Loufrani et al, , 2002 and systemic AAV has been shown to transduce smooth muscle, it should also be considered that stabilization of the vasculature may contribute to improvements observed in skeletal and cardiac muscle function (Ito et al, 2006).…”
Section: Aav Gene Therapymentioning
confidence: 99%